PENGENALAN MOCAF DAN OLAHANNYA SERTA STRATEGI BRANDING PRODUK BERBAHAN DASAR PANGAN LOKAL DALAM MENDUKUNG DIVERSIFIKASI PANGAN - Rosita Dewati; Yoesti Silvana Arianti; Yos Wahyu Harinta; Retno Widyastuti (Jurnal Abdimas Bina Bangsa, 2024)
The potential for developing mocaf as an effort to diversify food is supported by other government programs, young entrepreneurs. Entrepreneurial skills can be instilled from high school students in the Wonogiri Regency. This program is carried out by looking at the potential for building entrepreneurship by high school students from local food ingredients that can be developed, in this case mocaf flour and its processed products. Building products and businesses requires several strategies so that products gain a position in the market through product branding. Through product branding, a business can give the best impression of its product to consumers. This activity was declared successful with an indicator of increasing participants' knowledge and skills of 31.88%, which included increasing knowledge in terms of making mocaf flour and processing products as well as product branding. The implementation of this program is expected to be able to provide value added to cassava products and motivate students to develop cassava as a superior local product thereby improving the economic level of the community in Pracimantoro District, Wonogiri Regency